EFFECT OF KNOWLEDGE MANAGEMENT AND INTEGRITY ON COMPANY PERFORMANCE THROUGH MOTIVATION AS A MEDIATION VARIABLES IN PT KATELOC INDONESIA - Aga Yudho Prasetyo; Abdul Rivai; Suharto (The Institute of Academic Research and Publication (IARP), 2020)
This study aims to examine the effect of knowledge management and integrity on company performance through motivation as a mediating variable at PT. Kateloc Indonesia. The research sample was 283 employees. The data collection technique used questionnaires and data analysis used path analysis. The results showed that the knowledge management variable partially affected company performance. The integrity variable partially affects company performance. The motivation variable partially affects company performance. Knowledge management variables partially influence motivation. The integrity variable partially affects motivation. The influence of knowledge management on company performance is 0.548. The effect of knowledge management on performance through motivation is 0.676 X 0.868 = 0.587. In this case, the indirect effect is greater than the direct effect, so it can be said that the motivation variable is intervening. The direct effect of integrity on company performance is 0.659. Meanwhile, the influence of integrity on company performance through motivation is 0.782 X 0.868 = 0.679. In this case, the indirect effect is greater than the direct effect, so it can be said that the work motivation variable is intervening.